Humanised effector-null FcγRIIA antibody inhibits immune complex-mediated proinflammatory responses. Issue 2 (9th February 2019) - Chen, Bo; Vousden, Katherine A; Naiman, Brian; Turman, Sean; Sun, Hong; Wang, Shu; Vinall, Lisa M K; Kemp, Benjamin P; Kasturiangan, Srinath; Rees, D Gareth; Grant, Ethan; Hinrichs, Mary Jane; et al.
Abstract : Objective: Immune complexes (ICs) play a critical role in the pathology of autoimmune diseases. The aim of this study was to generate and characterise a first-in-class anti-FcγRIIA antibody (Ab) VIB9600 (previously known as MEDI9600) that blocks IgG immune complex-mediated cellular activation for clinical development. Methods: VIB9600 was humanised and optimised from the IV.3 Ab. Binding affinity and specificity were determined by Biacore and ELISA. Confocal microscopy, Flow Cytometry-based assays and binding competition assays were used to assess the mode of action of the antibody. In vitro cell-based assays were used to demonstrate suppression of IC-mediated inflammatory responses. In vivo target suppression and efficacy was demonstrated in FcγRIIA-transgenic mice. Single-dose pharmacokinetic (PK)/pharmacodynamic study multiple dose Good Laboratory Practice (GLP) toxicity studies were conducted in non-human primates. Results: We generated a humanised effector-deficient anti-FcγRIIA antibody (VIB9600) that potently blocks autoantibody and IC-mediated proinflammatory responses. VIB9600 suppresses FcγRIIA activation by blocking ligand engagement and by internalising FcγRIIA from the cell surface. VIB9600 inhibits IC-induced type I interferons from plasmacytoid dendritic cells (involved in SLE), antineutrophil cytoplasmic antibody (ANCA)-induced production of reactive oxygen species by neutrophils (involved in ANCA-associated vasculitis) and IC-induced tumour necrosis factor α and interleukin-6 production (involved in rheumatoid arthritis). In FcγRIIA transgenic mice, VIB9600 suppressed antiplatelet antibody-induced thrombocytopaenia, acute anti-GBM Ab-induced nephritis and anticollagen Ab-induced arthritis. VIB9600 also exhibited favourable PK and safety profiles in cynomolgus monkey studies. Conclusions: VIB9600 is a specific humanised antibody antagonist of FcγRIIA with null effector function that warrants further clinical development for the treatment of IC-mediated diseases.